2012
DOI: 10.1371/journal.pone.0036618
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Wwox Deletion in Mouse Mammary Gland by Means of Two Cre Recombinase Approaches

Abstract: Loss of WWOX expression has been reported in many different cancers including breast cancer. Elucidating the function of this gene in adult tissues has not been possible with full Wwox knockout models. Here we characterize the first conditional models of Wwox ablation in mouse mammary epithelium utilizing two transgenic lines expressing Cre recombinase, keratin 5-Cre (BK5-Cre) and MMTV-Cre. In the BK5-Cre model we observed very efficient Wwox ablation in KO mammary glands. However, BK5-Cre Wwox KO animals die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 44 publications
10
40
0
Order By: Relevance
“…The original publication of this K5-Cre transgene construct demonstrated activation in the epidermis of E15.5 embryos, as expected for a keratin 5 promoter (Ramirez et al , 2004). This transgene has been widely used to study targeted gene ablation in the epidermis and in other epithelial tissues such as the basal layer of the mammary gland duct (Eberl et al, 2012; Ferguson et al, 2012; Jackson et al, 2011; Omori et al, 2012). We crossed female IIA flox/flox mice with male K5-Cre/IIA flox/+ mice to obtain homozygous floxed mice (K5-Cre/IIA flox/flox ) which are subsequently referred to in this study as IIA KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original publication of this K5-Cre transgene construct demonstrated activation in the epidermis of E15.5 embryos, as expected for a keratin 5 promoter (Ramirez et al , 2004). This transgene has been widely used to study targeted gene ablation in the epidermis and in other epithelial tissues such as the basal layer of the mammary gland duct (Eberl et al, 2012; Ferguson et al, 2012; Jackson et al, 2011; Omori et al, 2012). We crossed female IIA flox/flox mice with male K5-Cre/IIA flox/+ mice to obtain homozygous floxed mice (K5-Cre/IIA flox/flox ) which are subsequently referred to in this study as IIA KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these publications were either silent regarding any observations of embryonic lethality, or in a few cases commented that pups were born at normal Mendelian ratios. One report, focused on mammary gland disruption of the tumor suppressor Wwox did report unexplained premature lethality in males and females that was independent of mammary gland development (Ferguson et al , 2012), possibly consistent with unrecognized K5-Cre expression at an earlier stage of development. We speculate that the lack of early embryonic defects in most published studies further reflects the critical and non-redundant roles of NM IIA in extraembryonic development, relative to other target genes that have been excised with this Cre transgene.…”
Section: Discussionmentioning
confidence: 96%
“…What is more, Wwox deletion did not affect tumorigenicity, nor did haploinsufficiency affect the mammary gland phenotype: It was concluded that Wwox might not be a classical tumor suppressor gene, but that rather loss of Wwox expression is associated with tumor progression. Nevertheless, Wwox knockdown in a mouse model resulted in impaired mammary branching morphogenesis (72). Similar observations, were made on a breast cancer cell line, where ectopical overexpression of WWOX gene in MDA-MB-231 breast cancer cells changed cell growth in Matrigel from tumor-like to branched structures, which resembled normal mammary duct formation (68).…”
Section: Biological and Clinical Implications Of Wwox In Breast Cancermentioning
confidence: 99%
“…For Wwox KO MMTV-Cre mice, significant deregulation of the genes involved in various cellular processes was observed in the mammary epithelium. Gene ontology enrichment analysis of the Biological Processes GO category identified WWOX-associated expression of Wnt signaling pathway genes, including significant upregulation of Wnt5a , which is also transcriptional target of the TGFβ/SMAD signaling pathway, skeletal system development/bone morphogenesis, genes associated with tissue remodeling, and cell migration as well as adhesion-related genes (for instance Timp2 and Timp3 upregulation) (72). An interesting strategy for elucidating WWOX function was employed by Aldaz et al Their study used a Multiexperiment Matrix bioinformatics tool to identify the top 100 genes positively-correlated with WWOX and the top 100 negatively-correlated genes based on approximately 4,800 samples of both normal and tumor tissues, as well as breast cancer cell lines, obtained from breast datasets.…”
Section: Biological and Clinical Implications Of Wwox In Breast Cancermentioning
confidence: 99%
“…78 On the other hand, although the Wwox +/- mouse on a C3H mammary tumor-susceptible genetic background exhibited enhanced mammary tumorigenesis, 79 mice with targeted deletions of Wwox in mammary tissue did not show a higher incidence of mammary tumors. 57,80 These conflicting results could be explained by the varying impact of ECM interactions with cancers- as Wwox was decreased in all tissues in the C3H mouse, but only in epithelial mammary cells in the conditional knockouts. In this way, the interactions with the ECM, such as that proposed by Gourley et al in ovarian caner cells, 28 could contribute to its tumor suppressor function in mammary cancers.…”
Section: Wwox: a Non-canonical Tumor Suppressormentioning
confidence: 99%